HUBUNGAN ASUPAN ENERGI MAKANAN DAN AKTIVITAS FISIK DENGAN KEJADIAN OBESITAS PADA ANAK SEKOLAH DASAR DI KOTA MANADO - Maki, Olvinda; Mayulu, Nelly; Djarkasi, Gregoria Sri Suhartati (Fakultas Pertanian, Universitas Sam Ratulangi, 2019)
Abstract Obesity is a serious illness that can cause emotional and social problems. A person is said to be overweight if the body is 10% to 20% normal body weight, while someone is called obese when overweight reaches more than 20% of normal body weight. Obesity is currently a world problem even WHO declares it a global epidemic (WHO, 2016) Meanwhile, children up to adolescents aged 5-18 years are classified as obese if the Z-Score BMI / U shows a number greater than 2 (WHO, 2016). This study was used with observational analytical research method with a research design used case control. The results showed that the picture of food energy intake and physical activity with the incidence of obesity in elementary school children was 39.3%, while for non-obese children it was 60.6%. Food energy intake in obese elementary school children is based on the level of adequacy of energy needs divided into 2 normal variables and more by 50%. And normal is 50%. There is a relationship between physical activity and the level of adequacy of energy and value (p = 0.000).Keywords: Obese, Energy Intake, Physical Activity